Exploring teachers' stories of writing: a narrative perspective. Issue 6 (18th August 2018) - Martin, Anne; Tarnanen, Mirja; Tynjälä, Päivi
ABSTRACT: This study takes a narrative perspective to examine teachers as writers and autobiographical creative writing as a way for promoting teachers' professional development. In a creative writing group for Finnish primary and secondary school teachers, the teachers expressed themselves and explored their lives and identities through autobiographical creative writing. The aim of this study was to examine the stories the teachers tell about their relationship to writing and the goals they set for their professional and personal development in the writing group. Through thematic analysis, seven descriptive themes were found in teachers' narratives of writing. Furthermore, based on the narrative analysis, a poem-like word image was composed. This study illustrates how literary methods diversify teachers' narratives. The findings shed light on teachers as creative writers and emphasise the connection between writing and well-being. Creative writing groups can be beneficial for teachers' professional development, identity work and well-being.